Efek Pre-Roasting Terhadap Parameter Kinetika Leaching Cr dari Limonit - Gyan Prameswara; Andi Nurfaadilah Ulfah; Cipta Panghegar Supriadi; Iga Trisnawati; Himawan Tri Bayu Murti Petrus (REACTOR: Journal of Research on Chemistry and Engineering, 2023)
Hydrometallurgical processes such as leaching of limonite ore to extract valuable metals including Ni and Co are often non-selective, including other metals in the leachate product. The leaching behavior of Cr from the chromite mineral contained in limonite ore is of concern due to the high Cr content of the leachate effluent. The pre-roasted process is frequently used to pre-treat limonite to increase the precious metal content. This study aims to determine the leaching behavior of Cr and the effect of pre-roasting on its kinetic parameters. The pre-roasting process was carried out at 280 and 610 oC for 4 hours. Observation of Cr leaching behavior was carried out in the leaching temperature range of 30-90 oC for 0-120 minutes using sulfuric acid solvent. The highest Cr recovery was achieved in pre-roasted ore leaching at 610 oC with leaching operating conditions of 2 M sulfuric acid, solid-liquid ratio of 5 g/50 mL, 200 rpm, for 120 minutes, at a leaching temperature of 90 oC, under these conditions Cr recovery reached 53.16%. The higher the roasting temperature, the lower the activation energy required for the leaching process. Cr leaching from raw and pre-roasted ore is controlled by the diffusion process through the ash layer with activation energies (EA) of 21.41, 18.64, and 14.71 kJ/mol for raw ore, pre-roasted ore 280 oC, and pre-roasted ore 610 oC, respectively. The comparison of kinetics data from several roasting products for atmospheric leaching feeds will provide industry with information to integrated pyro-hydrometallurgical process to increase Cr production from laterite.